2017
DOI: 10.5116/ijme.5898.309e
|View full text |Cite
|
Sign up to set email alerts
|

Patients with heart failure as co-designers of an educational website: implications for medical education

Abstract: ObjectivesTo identify the learning needs of patients with heart failure between outpatients follow-up visits from their perspective and to ascertain what they emphasize as being important in the design of an educational website for them. MethodsWe conducted a two-step qualitative study at Aarhus University Hospital, Denmark. Twenty patients with heart failure participated either in focus group interviews, diary writing, or video-recorded design sessions. Data on learning needs were collected in step 1 and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 33 publications
0
36
0
1
Order By: Relevance
“…On the one hand, the participants emphasised accuracy of the information, but on the other hand, they wanted the educational material to be simple and without medical terminology, which is a tension that has been noted in previous studies [ 33 ]. There is not seldom a conflict between, on the one hand, user requirements for a simple, intuitive design making use of everyday language; and on the other hand, requirements for accurate and complete medical information [ 33 ]. This is a contradiction that designers have to deal with; it may be tempting to choose simplicity as this is often asked for, but this may in the long run not meet the needs of the users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the participants emphasised accuracy of the information, but on the other hand, they wanted the educational material to be simple and without medical terminology, which is a tension that has been noted in previous studies [ 33 ]. There is not seldom a conflict between, on the one hand, user requirements for a simple, intuitive design making use of everyday language; and on the other hand, requirements for accurate and complete medical information [ 33 ]. This is a contradiction that designers have to deal with; it may be tempting to choose simplicity as this is often asked for, but this may in the long run not meet the needs of the users.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of DBR is cooperation in the design of ‘user-centred’ information systems and services in real settings [ 32 ]. Also, previous studies have shown that involving patients as co-designers may be useful in providing content which is experienced as meaningful in educational websites [ 33 ]. It is not well-known how the two care models, i.e., user-driven model, and self-care model, could be implemented in a portal for diabetes care in a culturally specific context, such as Iran.…”
Section: Contribution Of Technology To Self-managementmentioning
confidence: 99%
“…Nearly all studies, 65, mentioned a theory of PD. Clemensen et al's description of the PD methodology [28,29] was referenced in 10 of the reviewed studies [30][31][32][33][34][35][36][37][38][39], and that by Sanders and Stappers [13] was referenced in 9 [27,30,31,[40][41][42][43][44][45]. A handbook on PD by Simonsen et al [10] was referenced 7 times [27,31,36,[46][47][48][49].…”
Section: Overall Findingsmentioning
confidence: 99%
“…Design thinking aims to identify and solve problems in a systematic and collaborative way [12,13]. Collaborative design methods are widely used to improve electronic health (eHealth) [14], including the development of eHealth to assist heart patients with self-management [15][16][17][18][19]. However, design thinking research focusing on video communication software with heart patients is lacking.…”
Section: Design Thinkingmentioning
confidence: 99%